2012
DOI: 10.1016/j.neurobiolaging.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Screening for C9ORF72 repeat expansion in FTLD

Abstract: In the present study we aimed to determine the prevalence of C9ORF72 GGGGCC hexanucleotide expansion in our cohort of 53 FTLD patients and 174 neurologically normal controls. We identified the hexanucleotide repeat, in the pathogenic range, in 4 (2 bv-FTD and 2 FTD-ALS) out of 53 patients and one neurologically normal control. Interestingly, two of the C9ORF72 expansion carriers also carried two novel missense mutations in GRN (Y294C) and in PSEN-2 (I146V). Further, one of the C9ORF72 expansion carriers, for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
2
47
1
Order By: Relevance
“…Small repeat sizes of 20-22 were reportedly pathogenic in FTD, 8 Eight studies found no significant difference in mean repeat lengths between expansion-negative FTD cases and controls. [10][11][12][13][14][15][16][17] Sporadic FTD cases appear to show similar allele frequency distribution as controls, with the two-unit repeat being the most common, followed by the 5-repeat, 6-repeat, 7-repeat or 8-repeat unit. [12][13][14][15][16][17][18][19] Repeat range was higher in a Dutch study of 363 FTD patients where…”
Section: Introductionmentioning
confidence: 99%
“…Small repeat sizes of 20-22 were reportedly pathogenic in FTD, 8 Eight studies found no significant difference in mean repeat lengths between expansion-negative FTD cases and controls. [10][11][12][13][14][15][16][17] Sporadic FTD cases appear to show similar allele frequency distribution as controls, with the two-unit repeat being the most common, followed by the 5-repeat, 6-repeat, 7-repeat or 8-repeat unit. [12][13][14][15][16][17][18][19] Repeat range was higher in a Dutch study of 363 FTD patients where…”
Section: Introductionmentioning
confidence: 99%
“…6 The p.Y294C GRN variant is novel, and has not been detected in other patients or in controls; it was present in a patient with behavioral variant FTD and it is predicted to be damaging. 24 The p.A239T MAPT variant was also identified in a patient with behavioral variant FTD. 6 She had 2 brothers with C9ORF72 expansions without the MAPT variant, who demonstrated signs of MND.…”
mentioning
confidence: 97%
“…Interestingly, 2 patients have already been described with both C9ORF72 repeat expansions and a GRN variant (p.Y294C), 24 or a MAPT variant (p.A239T). 6 The p.Y294C GRN variant is novel, and has not been detected in other patients or in controls; it was present in a patient with behavioral variant FTD and it is predicted to be damaging.…”
mentioning
confidence: 99%
“…In a small number of FTD/ALS cases, coexistent mutations have been found in GRN, TARDBP, and MAPT. Ferrari et al (2012) reported two missense mutations, in GRN and in PSEN2, in two FTD hexanucleotide expansion carriers. Recently, Kaivorinne et al (2014) found the p. Ser292del variant and the C9orf72 expansion in two siblings with typical bvFTD without ALS signs, although a direct pathogenic role of the p. Ser292del variant cannot be demonstrated.…”
mentioning
confidence: 97%